2006
DOI: 10.1093/ps/85.7.1185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in ovo feeding egg white protein, β-hydroxy-β-methylbutyrate, and carbohydrates on glycogen status and neonatal growth of turkeys

Abstract: In ovo feeding (IOF), injecting dietary components into the amnion about 1 d prior to internal pipping, may enhance growth by altering glycogen status. This hypothesis was evaluated with 5 IOF solutions containing protein, beta-hydroxy-beta-methylbutyrate (HMB), and carbohydrate. Four IOF treatments were arranged as a factorial of 2 levels of egg white protein (EWP; 0 and 18%) and 2 levels of HMB (0 and 0.1%). An IOF solution of carbohydrates (S; 20% dextrin and 3% maltose) was evaluated for contrast purposes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
117
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 23 publications
12
117
2
2
Order By: Relevance
“…Tangara et al, (2010) have reported that injection of digestible carbohydrates and arginine to fertile duck eggs increased chick weight at 7 day after hatch by increasing embryo weight. Similar results were revealed by some researchers (Foye et al, 2006, McGruder et al, 2011b, Ohta et al, 1999. In conclusion, DL-methionine might be used as a substrate of in ovo feeding to obtain heavier chicks.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Tangara et al, (2010) have reported that injection of digestible carbohydrates and arginine to fertile duck eggs increased chick weight at 7 day after hatch by increasing embryo weight. Similar results were revealed by some researchers (Foye et al, 2006, McGruder et al, 2011b, Ohta et al, 1999. In conclusion, DL-methionine might be used as a substrate of in ovo feeding to obtain heavier chicks.…”
Section: Resultssupporting
confidence: 89%
“…Also, Ohta and Kidd, (2001) indicated that injection of different amino acid solution to 19 mm depth at the 6th day of incubation decreased hatchability from 88% to 70% but, injection to 13 mm depth did not affect hatchability and increased relative chick weight from 71.6% to 73.2%. Also it was reported that in ovo β-hydroxy-β-methyl butyrate injection to turkey eggs (Foye et al, 2006(Foye et al, , 2007 increased subsequent chick weight developed between 3% and 7% after hatch. Injection of DL-methionine to fertile broiler eggs provided 3.8% heavier chick compared to control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated that among BCAA, only leucine is capable of activating translation initiation factors and stimulating protein synthesis in skeletal muscles (Anthony et al, 2000). Thus, studies have focused especially on HMB (Foye et al, 2006(Foye et al, , 2007Tako et al, 2004) or BCAA (Bhanja and Mandal, 2005;Kita et al, 2015) supplementation in in ovo solution. However, leucine is not only a source for HMB formation, but also is an AA having extra proteolytic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, no data is available regarding the nano-Ag content in bones, either during prenatal or postnatal development. The key factor in chicken development is proper nutrition during embryogenesis (Foye et al, 2006). The main source of calcium for the growing embryo is its eggshell (Johnston and Comar, 1955).…”
Section: Introductionmentioning
confidence: 99%